Characterization of starch extracted from seeds of Cycas revoluta - Li, Kehu; Zhang, Tongze; Zhao, Wei; Ren, Huanhuan; Hong, Siqi; Ge, Yongyi; Corke, Harold (Frontiers in Nutrition, 2023)
The physicochemical and structural properties of two starch samples extracted from Cycad revoluta seeds were systematically investigated. The amylose contents of the two samples were 34.3 % and 35.5%, respectively. The spherical-truncated shaped starch granules possessed A-type crystallinity, and had an average diameter less than 15 μm. Compared to most commonly consumed cereal and potato starch, Cycad revoluta starch showed distinctive characteristics. For physicochemical properties, in the process of gelatinization, the Cycad revoluta starch showed similar viscosity profile to starches of some potato varieties, but Cycad revoluta starch had higher gelatinization temperature. Upon cooling, Cycad revoluta starch formed harder gels than rice starch. For structure, the molecular weight (indexed by Mw, Mn and Rz values), branching degree and the branch chain length distribution were determined. The results suggested that Cycad revoluta starch were different in structure from the main-stream starches. Notable differences in some starch traits between the two samples were recorded, which could be attributed to environmental factors. In general, this study provides useful information on the utilization of Cycad revoluta starch in both food and non-food industries.